شیكردنه‌وه‌ی جوگرافی بۆ دابه‌شبوون و هه‌ڵسه‌نگاندنی خزمه‌تگوزاریی خۆشگوزه‌رانی له‌شاری هه‌ڵه‌بجه‌ - حسین, پ.ی.د. به‌یان علی; علی, م.ی. هه‌ردی عبدالرحمن حمه‌ (Sulaimani Journal for Humanities, 2023)
It is known that most cities are characterized by various human activities, which lead to the occurrence of noise and boredom among their residents, so that the provision of services becomes an urgent necessity, in particular recreational services, through which a sense of comfort and reassurance can be felt, both physically and psychologically. This study is concerned with recreational services in the city of Halabja. Given the importance of these services and the positive aspects that characterize them, we will study this topic in an important population area, which is the city of Halabja. Presented by the measure of the individual share of recreational services, and at the end the research reached several results, the most important of which is that the total area allocated for recreational services in the city amounted to 273,215 square meters of all kinds (public parks, small parks, playgrounds, bodybuilding halls, cafes, swimming pools, and public libraries). Their area constitutes 1.06% of the total area of the city, and they are irregularly distributed among the various neighborhoods in the city.
Keywords: services; recreational services; Geographical distribution